Activated carbon biochar from municipal waste as a sorptive agent for the removal of polyaromatic hydrocarbons (PAHs), phenols and petroleum based compounds in contaminated liquids. (1st December 2019) - Sullivan, G.L.; Prigmore, R.M.; Knight, P.; Godfrey, A.R.
Abstract: Wastewater (WW) sludge cake is problematic to dispose of with treatment unable to remove organic pollutants. Typical disposal options include landfill or deposition on agricultural land, at considerable expense and environmental impact. Pyrolysis can recycle this waste to biochar however, additional unwanted organic pollutants are generated, differing in composition and volume according to the feedstock. These pollutants can be captured in solvent impingers or 'scrubbers' to avoid environmental release but lead to alternative waste. Both activated carbon and biochar are proven clean-up methods for organic pollutants with pine wood biochar showing changes in extraction selectivity with preparation temperature. Activated carbon biochar (ACB) from pine wood has also been successfully compared as a substitute at reduced cost and improved efficacy. To our knowledge, ACB from sludge cake has remained untested along with its application to clean-up solvent scrubbers. We have investigated this material from two WW treatment plants (UK and Ghana) as a sorbent, generated at 400 and 700 °C, to minimise contamination of liquids from pyrolysis and, petrochemicals in the event of a spill. This study confirmed the use and selective production of ACB for preferential clean-up of specific pollutants. Despite high temperature pine wood ACB proving most effective in removing petrochemical mixtures (>76%) extractions of equivalent repeatability and reasonable recovery were achieved with low temperature sludge cake ACB. This re-use of waste sludge cake offers improved thermochemical (recycling) and WW process efficiency, limiting the environmental impact and overall operational costs, minimising waste for disposal. Highlights: Activated carbon biochar of UK sludge cake is reliable for organic waste clean-up. Repeatability and sorption performance is dependent on feedstock and temperature. Sorbent can be used and selectively produced for clean-up of specific pollutants. UK sludge cake ACB has near similar recovery and better precision than pine wood. UK sludge cake can be re-used limiting cost, environmental impact and waste.